Volatility spillover and hedging effectiveness among crude oiland Islamic markets: Evidence from the Gulf region - Walid Mansour; Haykel Hamdi; Jihed Majdoub; Ikrame Ben Slimane (The European Journal of Comparative Economics (EJCE), 2020)
This paper studies the volatility spillover between oil price and conventional and Islamic stock markets. We use a sample of five standard MSCI indexes and their Islamic counterparts from five countries from the Gulf region (Jordan, Kuwait, Oman, Qatar, UAE) and Brent crude oil price index, obtained from MSCI and Energy Information Administration (EIA), to represent the world oil market. We analyze the spillover effects between crude oil and Islamic and conventional indexes using the bivariate VARMA-BEKK-GARCH model of Ling and McAleer (2013), which includes spillover effects in return and variance. Our findings show particular specificities of Islamic marketplaces in reducing the volatility transmission and lowering the volatility persistence, which gives the investors and market participants an opportunity in terms of international diversification and hedging effectiveness. Although our results are indicative of crude oil hedging strategies, they also testify the distinction of Islamic financial markets and raises the issue of strategic posture and competitiveness in the global financial system.
Keywords: G11; G15; G32; E3; 330; Volatility spillover; Gulfregion; Oil price; Islamic finance